Innovative circular economy approaches in e-waste management: a case study of telkomcel timor leste - Damiao Maia, Graciano Andre; Lubis, Ratna Lindawati; Yunita, Irni (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2024)
This study evaluates the application of circular economy principles in managing e-waste at Telkomcel Timor Leste, a leading telecommunications company in the country. Timor Leste is facing increasing challenges in e-waste management due to the growing use of technological devices, which contributes to the rising volume of electronic waste. Inadequate management of e-waste poses significant environmental and health risks, including pollution and the leaching of harmful substances into the soil and water. The study uses a mixed-methods approach, including secondary data analysis and in-depth interviews with key stakeholders at Telkomcel, involving 4 respondents from various stackholder related to waste management and sustainability. The analysis focuses on Telkomcel's strategies in implementing circular economy practices, such as device refurbishment, recycling programs, and internal policies. The findings reveal that while Telkomcel has taken significant steps toward adopting a circular economy model, challenges remain, including limited infrastructure, low public awareness, and insufficient recycling facilities. Notably, Telkomcel has initiated internal policies promoting e-waste collection, repair, and reuse of devices, yet the company faces barriers in scaling these efforts. The study highlights the importance of strengthening collaboration with third-party recycling partners, expanding the recycling infrastructure, and raising public awareness through education campaigns. This research is significant in the context of the United Nations Sustainable Development Goals (SDGs), particularly SDG 12 (Responsible Consumption and Production) and SDG 13 (Climate Action), as it emphasizes the need for sustainable e-waste management practices to mitigate environmental impact and contribute to long-term resource efficiency. The study concludes with recommendations for Telkomcel to enhance its sustainability efforts by improving infrastructure, increasing public education on e-waste recycling, and advocating for stronger government regulations. These efforts are expected to support sustainable development in Timor Leste while minimizing the environmental consequences of improper e-waste disposal.